Kajian Feminisme dalam Novel Nadira Karya Leila S. Chudori - Nora, Risma; Shomary, Sudirman (UIR Press, 2023)
Feminism not only discusses the movement of female characters to obtain the same status as men but also about the description of women based on their physical characteristics, behavior and position. This research includes a qualitative approach. The type of research is library research. The method used is the descriptive method. The research technique is by applying hermeneutic techniques. Based on the results of the analysis, it can be concluded that the biological aspect is related to the general physical characteristics of women with beautiful faces and ideal body shapes. The psychological aspect of the character's thinking occurs as a result of the loss of the mother and the breakdown of the household. The taste of the differences in taste between the characters is caused by the nature of themselves and their parents, the living environment of the female characters in Indonesia and Amsterdam, the age differences between the characters and current fashion. Pressured feelings show anger, emotion, disappointment, sadness, downturn and anxiety. Social aspects regarding the process of socialization, well-established relationships between the figures, higher education with a disciplined and strict education pattern. Social duties are about responsibility in the household and social environment. The social class of women is classified as upper middle class women who work in offices as permanent employees.